Generation Z's Interest in Digital Wallet Payments in Islamic Mobile Banking During a Pandemic - Ghoynaqi, Ria Ida Maf’ula; Saibil, Defi Insani (Universitas Islam Negeri (UIN) Walisongo Semarang, 2022)
Purpose - This research was conducted to see interest in digital wallet payments in mobile banking applications using the TAM and TPB theories.Methods - This study tested the hypothesis using Structural Equation Modeling (SEM) with the SmartPLS 3.0 application.Results - The results showed that there was a positive influence on perceived ease of use, perceived usefulness, and subjective norms and significant on intention to use. Meanwhile, attitudes do not affect the intention to use Islamic mobile banking. So attitude is not a factor in Generation Z's intention to use mobile banking in digital wallet transactionsImplications - The population in this study is the Z generation which is carried out in the Special Region of Yogyakarta. A total of 111 respondents used purposive sampling method in determining the population sample.Originality - Respondents in this study have criteria, namely users of Islamic mobile banking and generation Z digital wallets conducted in the Special Region and during the Covid-19 pandemic.